Preparation of bio-oil-based polymer microspheres for adsorption Cu2+ and its adsorption behaviors. Issue 7 (8th June 2021) - Tian, Xin; Zhang, Luming; Li, Hengxiang; Zhang, Xiaohua; Wang, Qun; Jin, Li'e; Cao, Qing
Abstract: Bio oil, a liquid derived from pyrolyzing biomass, which is rich in oxygen and hard to utilize. Herein, a kind of bio-oil-based polymer microspheres for adsorbing Cu 2+ was successfully synthesized. Pretreated bio-oil were cross-linked with phenol, formaldehyde into a polymer. Then the polymer was encapsulated into microspheres by sodium alginate sol-gel. In comparison with the microspheres produced without bio-oil and unpretreated bio-oil but under identical steps, the microspheres obtained with pretreated bio-oil had the maximum adsorption capacity of 194.54 mg g −1 for Cu 2+ (293 K), which exceeded most capacity reported in the literature. The adsorption process followed pseudo-second-order kinetics, and fitted well with the Langmuir isotherm model. It was also an endothermic and spontaneous process. The structure and morphology were also characterized by fourier transform infrared (FT-IR) spectrometer, thermal gravimetric (TG), N2 adsorption–desorption isotherm analyses, scanning electron microscope (SEM), elemental analyzer, X–ray photoelectron spectroscopy analysis (XPS). This work provides a novel way of utilizing bio-oil and choosing adsorbents for the removal of heavy metals. The bio-oil based polymer microspheres were prepared and exhibited excellent adsorption of Cu 2+ . This phenomenon was attributed to the fact that the presence of oxygen-containing functional groups such as –OH, and –SO3 in the microspheres provided sites of action for chelation with heavy metal ions. Graphical Abstract: uf0001